The Precipitated Electrons in the Region of Diffuse Aurora Driven by Ionosphere‐Thermosphere Collisional Processes - George V. Khazanov; Alex Glocer; Mike Chu (Geophysical Research Letters)
Abstract Traditionally, it is widely assumed that the source of electron precipitation in the region of diffuse aurora is wave‐particle interaction processes in the Earth's plasmasheet. It is difficult to imagine that ionosphere‐thermosphere system is also actively involved in the formation of electron precipitation and provides a very noticeable energy contribution to this process. In this study, we use specifically designed simulation scenarios of the SuperThermal Electron Transport code to clearly distinguish between the magnetospheric and ionospheric contributions to the precipitating electrons in the region of diffuse aurora. It is demonstrated that atmospheric collisional processes and the overall magnetosphere‐ionosphere‐atmosphere energy circulation dynamics, with the participation of two magnetically conjugate hemispheres, play a very important role in the formation of electron energy fluxes that are coming from the magnetosphere.